2013
DOI: 10.1016/j.jenvman.2013.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a model azo dye in submerged anaerobic membrane bioreactor (SAMBR) operated with powdered activated carbon (PAC)

Abstract: This work investigated the anaerobic degradation of the model azo dye Remazol Yellow Gold RNL in an upflow anaerobic sludge blanket reactor (UASB) and two submerged anaerobic membrane (SAMBR) bioreactors, one of which (SAMBR-1) was operated with powdered activated carbon (PAC) in its interior. The reactors were operated at 35 °C with a hydraulic retention time of 24 h in three operational phases, aimed to assess the effect of external sources of carbon (glucose) or redox mediator (yeast extract) on the removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 31 publications
(36 reference statements)
2
24
0
1
Order By: Relevance
“…During phases 4 (with yeast extract) and 5 (without yeast extract) the reactors were fed raw textile wastewater (without dilution) and the presence of yeast extract led to color removal efficiencies 3 times higher in SAMBR-1 and 2.7 higher in SAMBR-2. These results are in accordance with the literature (Baêta et al, 2012;Baêta et al, 2013), confirming that the kinetics of azo dye (one on the many dye classes found in textile wastewater) degradation is accelerated in the presence of redox mediators such as riboflavin, which have intermediate reduction potential values. It is important to highlight that there is only a handful of studies evaluating the effect of redox mediators on color removal of real textile wastewater.…”
Section: Color Efficiency Removal (%)supporting
confidence: 92%
See 2 more Smart Citations
“…During phases 4 (with yeast extract) and 5 (without yeast extract) the reactors were fed raw textile wastewater (without dilution) and the presence of yeast extract led to color removal efficiencies 3 times higher in SAMBR-1 and 2.7 higher in SAMBR-2. These results are in accordance with the literature (Baêta et al, 2012;Baêta et al, 2013), confirming that the kinetics of azo dye (one on the many dye classes found in textile wastewater) degradation is accelerated in the presence of redox mediators such as riboflavin, which have intermediate reduction potential values. It is important to highlight that there is only a handful of studies evaluating the effect of redox mediators on color removal of real textile wastewater.…”
Section: Color Efficiency Removal (%)supporting
confidence: 92%
“…Other works published by our research group (Baêta et al, 2013) have shown that powdered activated carbon (PAC) can be used as adsorbent of toxic byproducts of anaerobic degradation (e.g., aromatic amines) of textile dyes, as well as of some intermediate VFAs, thereby reducing thermodynamic constraints and enhancing the methanogenic and acetogenic activities. A statistical analysis of COD data (Figure 2) in the reactors SAMBR-1 (with PAC) and SAMBR-2 (without PAC) during phases 1, 2 and 4 shows that PAC influenced only phase 1 since there were no statistically significant differences (p-value > 0.05) for the other phases.…”
Section: Effect Of the Dilution Factor (Df) And Hydraulic Retention Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Baeta et al [24] showed that PAC had a great capacity to adsorb some intermediate VFA such as acetic (Q max = 5.80 mg/g), butyric (Q max = 5.19 mg/g) and…”
Section: Cod Removal In the Combined Treatment Systemsmentioning
confidence: 99%
“…Lately, carbon based materials, such as granular (Van der Zee et al 2003) and powder activated carbon (Baêta et al 2013), black carbon (Xu et al 2013;Gong et al 2014), biochar (Oh et al 2013), activated carbon fibers (Amezquita-Garcia et al 2013;Ríos Del Toro et al 2013), carbon nano-tubes and carbon xerogels (Pereira et al 2014), as well as graphene oxide (Colunga et al 2015) have also been applied as RM to increase the redox conversion of different contaminants.…”
Section: Introductionmentioning
confidence: 99%